2005
DOI: 10.4049/jimmunol.174.11.6918
|View full text |Cite
|
Sign up to set email alerts
|

Association of B-1 B Cells with Follicular Dendritic Cells in Spleen

Abstract: Although CD5+ B-1 B cells have been recognized as an infrequent B cell subset in mice for many years, attempts to identify their histologic location in normal mouse spleen have proven difficult due to both their paucity and low level expression of CD5. In this study we have studied VH11/DH/JH gene-targeted mice, VH11t, that develop elevated numbers of CD5+ VH11/Vk9 B cells with an anti-phosphatidylcholine (anti-PtC) autoreactive specificity, allowing B-1 B cell detection by anti-PtC Id-specific Abs in spleen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 67 publications
3
41
0
Order By: Relevance
“…22,23 The Rag2 and common g chain double-deficient mice (Rag2 2/2 g 2/2 ) mice were obtained from Taconic. All mice were maintained under specific pathogen-free conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 The Rag2 and common g chain double-deficient mice (Rag2 2/2 g 2/2 ) mice were obtained from Taconic. All mice were maintained under specific pathogen-free conditions.…”
Section: Methodsmentioning
confidence: 99%
“…21 Analysis of Vh11 knock-in mice confirmed that B cells expressing the Vh11 knock-in allele give rise to B1 cells, whose population is expanded dramatically in the Vh11 knock-in mice. 22 Here, we report that IRF4-deficient mice expressing the Vh11 knock-in allele (IRF4 There is an Inside Blood commentary on this article in this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Although physiologic differences between murine and human B-cell populations exist, prohibiting defi nitive conclusions ( 48 ), similarities are also appreciated that affect structural restriction of the BCRs, the polyreactivity toward autoantigens, expression of CD5, and the presentation as activated antigen-experienced B cells ( 3 , 9 , 49 ). B-1 cells can induce and associate with FDCs in mice; however, traffi cking routes of these cells have not been thoroughly analyzed ( 50 ).…”
Section: Research Articlementioning
confidence: 99%
“…Previous studies showed that peritoneal B-1a cells can migrate to the spleen (36,37) and that those present in the pleural cavity can migrate to mediastinal lymph nodes (38). To determine whether the peritoneal B-1a subsets differ in their migratory potential, we adoptively transferred equal numbers of sort-purified subsets i.p.…”
Section: Pc1mentioning
confidence: 99%